The form and function of humor in mark twant's short stories entitled the celebrated jumping frog of calaveras county and steamboat race - Ade Mukhlisin (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2016)
wt,1/nis,c.1